Accessibility evaluation of assembly operations in confined space based on digital human model - Wang, Silu; Li, Jianguang; Yin, Mingyue; Wu, Qian (International journal of industrial ergonomics, 2025)
The confined spaces (CS) of large equipment are typically compact with intricate operational environments, which significantly affect the accessibility, efficiency, and operational quality of workers. Spatial accessibility evaluation, as a critical indicator of worker safety and product design optimization, is an essential part of equipment product design. This study proposes a comprehensive evaluation method based on digital human models (DHMs) and virtual reality systems (VRS) for the quantitative analysis of operational accessibility in CS. The method integrates DHMs and ergonomics data to analyze human dynamics, path accessibility, operational accessibility, and visibility. It defines the spatial restriction ratio (SRR) and the operational freedom ratio (OFR), and combines directional weight coefficients for specific operation types with REBA posture ratings to construct a multi-dimensional quantitative evaluation system. The experiment was based on 6 confined units and 11 operations of an equipment, recruiting 10 subjects to simulate real operations through VRS to validate the effectiveness of the method. The results of the tests demonstrate that the method can effectively evaluate the operation accessibility in CS, optimize the product layout, reduce the risk of musculoskeletal injuries for workers, and provide theoretical support for the iterative design of industrial equipment. It promotes the transition of operational accessibility evaluation in CS from experience-driven to data-driven precision upgrades, offering new perspectives and methodological support for the spatial layout optimization and scientifically reasonable operation planning of complex industrial products. •A comprehensive evaluation method using DHMs and Virtual Reality System to quantitatively analyze restriction degree in confined space is proposed.•The Spatial Restriction Ratio is the ratio of the volume of the human bounding box to the volume of confined united space which is based on the human operational posture and spatial size.•A comprehensive evaluation indicator for the Operational Freedom Ratio is presented based on the tool usage for specific operation types and the direction weight coefficients of the worker's arm motion sets.•Shifting confined space operational accessibility evaluation from experience-driven to data-driven precision upgrades.